The Other Heading of Europe: From Miłosz to Derrida - Gornykh, Andrei (Eidos. A Journal for Philosophy of Culture, 2025)
The article explores a conceptualization of Eastern Europe at the intersection of literature and philosophy, focusing on two texts: The Issa Valley (1955) by Czesław Miłosz and The Other Heading (1991) by Jacques Derrida. In this context, Eastern Europe can be understood as a historical topos situated between Russian imperial violence concerning civil liberties and Western Enlightenment rationality, which can lead to the homogenization of cultural landscapes and the erasure of internal borders. These landscapes and borders are essential for the individual’s search for identity and the formation of a dense network of mutual dependency and historically determined communities that culturally shape specific social subjects, thereby resisting any imperial influence.